Spectral Dynamic Analysis of Buckling Restrained Brace (BRB) Configurations in an Irregular Building - Orellana, Gianjairo M. (2024)
This research covers a comparison between different configurations for the application of Restricted Buckling Brace (BRB) through the dynamic analysis of an irregular building that does not comply with the maximum drifts in one of its directions and is reinforced with the different distributions. The reinforcement with BRB was achieved with the three distributions analyzed and the guidelines of the Peruvian standard E.030 2018 were met. In that sense, the reduction of the maximum inelastic story drifts with the BRB V configuration was 25.64%. The reduction of maximum inelastic story drifts with the Inverted BRB V configuration was 27.92%. While the reduction of maximum inelastic story drifts with the BRB X configuration was 28.71%. Thus, the configuration with the best results was the BRB in X.